2013
DOI: 10.1017/s0954579412001241
|View full text |Cite
|
Sign up to set email alerts
|

Gene × Environment effects of serotonin transporter, dopamine receptor D4, and monoamine oxidase A genes with contextual and parenting risk factors on symptoms of oppositional defiant disorder, anxiety, and depression in a community sample of 4-year-old children

Abstract: . (2013). Gene x environment effects of serotonin transporter, dopamine receptor D4, and monoamine oxidase A genes with contextual and parenting risk factors on symptoms of oppositional defiant disorder, anxiety, and depression in a community sample of 4-year-old children. Development and Psychopathology 25, 555-575.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
39
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(49 citation statements)
references
References 126 publications
(226 reference statements)
9
39
1
Order By: Relevance
“…There have been a number of studies of MAOA VNTR polymorphisms as risk factors for MDD, but metaanalysis confirmed this association only in Asian populations (Fan et al, 2010). In preschool boys (N=97), increased caregiver depression or family conflict was associated with increased depression symptoms in boys with low-MAOA polymorphism genotypes (Lavigne et al, 2013). Our study did not use an animal model of a childhood behavior disorder, but, using the RDoC framework for integrating basic research and diagnostic criteria (Garvey et al, 2016; Cuthbert and Insel, 2013; Maestripieri and Lilienfeld, 2016), the results can be seen applicable to the “negative valence” construct dimension relevant to depression, as well as other developmental diagnoses.…”
Section: 0 Discussionmentioning
confidence: 99%
“…There have been a number of studies of MAOA VNTR polymorphisms as risk factors for MDD, but metaanalysis confirmed this association only in Asian populations (Fan et al, 2010). In preschool boys (N=97), increased caregiver depression or family conflict was associated with increased depression symptoms in boys with low-MAOA polymorphism genotypes (Lavigne et al, 2013). Our study did not use an animal model of a childhood behavior disorder, but, using the RDoC framework for integrating basic research and diagnostic criteria (Garvey et al, 2016; Cuthbert and Insel, 2013; Maestripieri and Lilienfeld, 2016), the results can be seen applicable to the “negative valence” construct dimension relevant to depression, as well as other developmental diagnoses.…”
Section: 0 Discussionmentioning
confidence: 99%
“…Levels of MAO-A in the brain of patients with major depressive disorder, measured using positron emission tomography (PET), are elevated by an average of 34 %. Recently, evidence has indicated that the MAOA gene may associate with depression [49] and stress [50]. Evidence regarding whether lower or higher transcriptional efficiency of the MAOA gene, is positively associated with psychological pathology, has however, been mixed.…”
Section: Monoamine Oxidase-amentioning
confidence: 99%
“…47 Specifically, dopamine receptor and dopamine pathway, serotonin transporter, and COMT genetic variants interact with environmental factors to influence cognitive and behavioral functioning in various childhood populations. 18,48-58 Although the higher activity enzyme genotype (GG) is generally associated with a reduction in executive cognition, it is also associated with better stress resiliency, indicating that stressful environmental factors may overwhelm the direct effects the COMT genotype has on cognition 59 Because a TBI often leads to increased family burden 42,60,61 , the potential stress resiliency effects of the high activity genotype (GG) may outweigh the effects on executive cognition. Future studies should evaluate the interaction of genetics and environmental and other factors on recovery.…”
Section: Discussionmentioning
confidence: 99%